Lower-limb exoskeletons for individuals with chronic spinal cord injury: findings from a feasibility study. (January 2016) - Benson, Ian; Hart, Kirsten; Tussler, Dot; van Middendorp, Joost J
Objective: To assess the feasibility of conducting a well-powered trial evaluating the neurological and functional effects of using an exoskeleton in individuals with chronic spinal cord injury. Design: A longitudinal, prospective, self-controlled feasibility study. Setting: Specialist Spinal Cord Injuries Centre, UK; 8 months during 2013–2014. Subjects: Individuals with chronic motor complete or incomplete spinal cord injury. Interventions: Enrolled subjects were assigned to 20 exoskeleton (ReWalk™, Argo Medical Technologies Ltd, Yokneam Ilit, Israel) training sessions over a 10-week training period. Main measures: Feasibility measures, clinical and mobility outcome measures and measures appraising subjects' disability and attitude towards assistive technology were assessed before, during and after the study. Descriptive statistics were applied. Results: Out of 60 candidates, ten (17%) were enrolled and five (8%) completed the training programme. Primary reasons for not enrolling were ineligibility ( n = 24, 40%) and limited interest to engage in a 10-week training programme ( n = 16, 27%). Five out of ten enrolled subjects experienced grade I/II skin aberrations. While walking speeds were higher and walking distances were longer in all exoskeleton users when compared with non-use, the exoskeleton did generally not meet subjects' high expectations in terms of perceived benefits. Conclusions: The conduct of a controlled trial evaluating the benefits of using exoskeletons that require a lengthy user-commitment to training of individuals with chronic motor complete or incomplete spinal cord injury comes with considerable feasibility challenges. Vigilance is required for preventing and detecting medical complications in spinal cord injury exoskeleton users.